2013
DOI: 10.1007/s11881-013-0083-y
|View full text |Cite
|
Sign up to set email alerts
|

Project DyAdd: Implicit learning in adult dyslexia and ADHD

Abstract: In this study of the project DyAdd, implicit learning was investigated through two paradigms in adults (18-55 years) with dyslexia (n = 36) or with attention deficit/hyperactivity disorder (ADHD, n = 22) and in controls (n = 35). In the serial reaction time (SRT) task, there were no group differences in learning. However, those with ADHD exhibited faster RTs compared to other groups. In the artificial grammar learning (AGL) task, the groups did not differ from each other in their learning (i.e., grammaticality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 103 publications
3
39
2
Order By: Relevance
“…This pattern of differences between the groups may indicate that extraneous factors, such as impaired coordination or motor learning (Ramus, Pidgeon, & Frith, ), influence the performance of children with dyslexia on the serial reaction time tasks. This conjecture is in line with findings from some previous studies in children with dyslexia (Vakil, Lowe, & Goldfus, ) and adults (Henderson & Warmington, ; Laasonen et al, ). Finally, it should be noted that individual differences in procedural learning did not correlate with word or non‐word reading in either group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This pattern of differences between the groups may indicate that extraneous factors, such as impaired coordination or motor learning (Ramus, Pidgeon, & Frith, ), influence the performance of children with dyslexia on the serial reaction time tasks. This conjecture is in line with findings from some previous studies in children with dyslexia (Vakil, Lowe, & Goldfus, ) and adults (Henderson & Warmington, ; Laasonen et al, ). Finally, it should be noted that individual differences in procedural learning did not correlate with word or non‐word reading in either group.…”
Section: Discussionsupporting
confidence: 92%
“…This conjecture is in line with findings from some previous studies in children with dyslexia (Vakil, Lowe, & Goldfus, 2015) and adults (Henderson & Warmington, 2017;Laasonen et al, 2014). Finally, it should be noted that individual differences in procedural learning did not correlate with word or non-word reading in either group.…”
Section: Procedural Learningsupporting
confidence: 92%
“…However, several previous studies have found no abnormalities in SRT performance or in reactions to conflict on the transfer block, as indexed by mean RTs, in this population (Karatekin et al, 2009; Laasonen et al, 2014; Vloet et al, 2010; but see Barnes et al, 2010 1 ). This is likely in part because the standard performance measure used in SRT is MRT.…”
contrasting
confidence: 52%
“…However, passive exposure to corresponding sound and letter sequences may also occur, resulting in associated orthographical and phonological representations that have been implicitly acquired and become part of an automatized procedure in the decoding process (Snowling, 1980). Children with reading difficulties exhibit lower performance on certain types of implicit learning tasks (Folia et al, 2008; Laasonen et al, 2014; Vicari et al, 2005). Thus, associative learning has been studied as a predictor of reading skills (Muter, Hulme, Snowling, & Stevenson, 2004).…”
mentioning
confidence: 99%